Search for top squarks in R-parity-violating supersymmetry using three or more leptons and b-tagged jets - Chatrchyan, S; Khachatryan, V; Sirunyan, A M; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; Ghete, V M; et al. (Physical review letters, 2013)
A search for anomalous production of events with three or more isolated leptons and bottom-quark jets produced in pp collisions at √s=8 TeV is presented. The analysis is based on a data sample corresponding to an integrated luminosity of 19.5 fb(-1) collected by the CMS experiment at the LHC in 2012. No excess above the standard model expectations is observed. The results are interpreted in the context of supersymmetric models with signatures that have low missing transverse energy arising from light top-squark pair production with R-parity-violating decays of the lightest supersymmetric particle. In two models with different R-parity-violating couplings, top squarks are excluded below masses of 1020 GeV and 820 GeV when the lightest supersymmetric particle has a mass of 200 GeV.